Do Antifungals and Local Anesthetic Affect the Efficacy of Antibiotic Dipping Solution?. Issue 5 (23rd April 2021) - Mishra, Kirtishri; Bukavina, Laura; Long, Lisa; Sherif, Rania; Gupta, Shubham; Muncey, Wade; Thirumavalavan, Nannan; Ghannoum, Mahmoud; Loeb, Aram
ABSTRACT: Background: The rates of infection after inflatable penile prosthesis (IPP) range from 1% to 3%; however, with changes in antibiotic practice intraoperatively and the incorporation of local anesthetic dips, it is unclear whether this incidence of infection is affected. Aim: To evaluate whether the utilization of local anesthetic dips and antifungal solutions affect the efficacy of previously established dips across multiple species and strains. Methods: Strains of four different species of bacteria and one fungus were prepared in a standardized confluency. A standardized, and sterile protocol was used to punch out 6mm circular discs from the reservoir of a Coloplast Titan device. The discs were submerged in a standardized concentration of antimicrobials (combinations of Bactrim, Rifampin + Gentamicin, Vancomycin, Zosyn, and Amphotericin B) and plated. The zone of inhibition (ZOI) was measured at 24, 48, and 72 hours. Five repetitions of each organism was performed (>1700 discs), and the mean ZOI was calculated. Saline and DMSO were used as control on each plate. Outcomes: Main outcome was the ZOI identified with each antibiotic solution, and the secondary outcome was the efficacy of the antibiotic over the course of 72 hours. RESULTS: Difference in antibiotic efficacy was seen when each bacterial species was evaluated separately, with rifampin and gentamicin having less efficacy towards all organisms other than S. epidermidis . When looking specifically at the Candida species, amphotericin B was significantly better than other antibiotic solutions. In regards to efficacy of antibiotics over 72 hours, all treatment groups showed a decrease in ZOI over time. However, treatment groups that included rifampin demonstrated the ability to inhibit S. aureus and S. epidermidis over the 72-hour period. Clinical Implications: To improve clinical practice and alleviate concerns that incorporation of local anesthetic and antifungals may decrease the efficacy of antibiotic solutions. Strengths and Limitations: A major strength of the study is that it is the most robust and scientifically sound study performed on this topic with approximately 1700 repetitions. It is also the first study of its kind to include a wide spectrum of bacterial and fungal strains and antibiotic solutions along with temporal data on drug elution over a 72-hour period. A limitation of the study is the in vitro model, and this needs to be validated in a clinical setting. CONCLUSIONS: Dipping prosthetics in antifungal and local anesthetic does not decrease the efficacy of the antimicrobials. The drug elution capabilities of the hydrophilic coating lasts primarily for 24-48hours.